2012
DOI: 10.1097/iae.0b013e318217fffb
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Of, Risk Factors For, and Combined Mechanism of Late-Onset Open-Angle Glaucoma After Vitrectomy

Abstract: Lens extraction is a strong risk factor for the development of late-onset OAG after uncomplicated PPV. While the overall incidence of OAG development after PPV is substantial, it is more so among eyes that have had CE. The absence of substantial OAG incidence in phakic patients points toward a combined mechanism for late-onset post-PPV OAG involving PPV and CE at any time. Preoperative PPV counseling should include the risk of glaucoma development in addition to cataract development and the connection between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 33 publications
4
64
2
7
Order By: Relevance
“…Remarkably, patients who had cataract surgery prior to vitrectomy developed glaucoma an average of 28 months earlier than those who were phakic at the time of vitrectomy and later had cataract surgery. More detailed follow-up studies supported the increased risk of glaucoma after vitrectomy and cataract surgery [18,19]. However, other studies conclude that the risk of glaucoma does not increase significantly after vitrectomy and cataract surgery.…”
Section: Vitrectomy Cataract and Glaucomamentioning
confidence: 94%
“…Remarkably, patients who had cataract surgery prior to vitrectomy developed glaucoma an average of 28 months earlier than those who were phakic at the time of vitrectomy and later had cataract surgery. More detailed follow-up studies supported the increased risk of glaucoma after vitrectomy and cataract surgery [18,19]. However, other studies conclude that the risk of glaucoma does not increase significantly after vitrectomy and cataract surgery.…”
Section: Vitrectomy Cataract and Glaucomamentioning
confidence: 94%
“…Several groups have shown that vitrectomy and cataract surgery significantly increase IOP and the risk of developing POAG, 55,56 which is due to exposure of the TM and SC to a higher level of oxygen causing oxidative damage to these tissues. 57,58 We demonstrated in vitro in an aging model of hyperoxia that it altered eNOS and its phosphorylation status and resulted in reduced NO production.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of glaucoma after pars plana vitrectomy has been reported between 11.6 and 20% [66, 87]. Acute post operative increase in IOP can be due to replacement with intra ocular tamponade (Gas/Silicone oil), use of intra operative endo-photocoagulation or post operative fibrinous inflammatory reaction.…”
Section: Glaucoma After Retinal Surgerymentioning
confidence: 99%